MEASURING THE SATISFACTION AND LOYALTY LEVEL OF MILLENNIAL FARMERS: A CASE STUDY ON SUGARCANE FARMING IN THE PARTNERSHIP BETWEEN FARMER AND PTPN XI EAST JAVA - Umaiya, Ahadyah Ayu; Irham, Irham; Perwitasari, Hani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The PTPN XI’s sugarcane supply in the last five years has tended to decline. A strong partnership between sugarcane farmers and PTPN XI can be an alternative solution to overcome the scarcity of the sugarcane supply by being shown high satisfaction and loyalty. The aims of this study are: 1) to compare the level of satisfaction of millennial and old sugarcane farmers to the performance of PTPN XI and 2) to compare the level of loyalty of millennial and old sugarcane farmers in partnership. The millennial and old sugarcane farmers' satisfaction levels are used to analyze CSI, gap analysis, Z-test, and IPA. The loyalty levels used average table analysis and Z-test. The study samples were obtained from four sugar mills areas of PTPN XI: Asembagoes, Soedhono, Wonolangan, and Pradjekan.  The results showed that the satisfaction level category of millennial farmers was quite satisfied (65.68%), while the satisfaction level of old sugarcane farmers was satisfied (67.04%). Statistically, the results of the Z-test showed a significance value of 0.021. There was a difference in the average satisfaction level between millennial and old sugarcane farmers, where the satisfaction level of sugarcane farmers was higher than millennials. However, the study found that the loyalty of old sugarcane farmers was more elevated than millennials using the Z-test with a significance value of 0.011. Through this study, it is expected that the partnership between PTPN XI and the sugarcane farmers is getting better quality to achieve increased sugar production.